Role of International Trade and Supply Chain Management in Economic Development of Countries - Askar Nailevich Mustafin; Dilyara Ildarovna Makhmutova (International Journal of Supply Chain Management, 2019)
Abstract- International cooperation and the development of globalization have a favorable impact on the market economy: there is a cultural, moral, social, political and economic unification of all cities, countries and continents. The consequences of these processes are the further integration of countries into international trade, which continues to take an increasingly important role in the economies of developed countries by using the supply chain strategy.Practical experience of developed countries demonstrates that international trade has a huge impact on the level of the country well-being. Such indicators of foreign trade as the changes in exports, imports and foreign trade balances of China, Russia, the United States and Germany, are presented in the paper. According to the results of the economic study of four developed countries-leaders in international trade: China, Russia, the United States and Germany, the team of authors proposed a ranking of these countries in the order of importance of foreign trade for their economies.